Absorptive Capacity and Intellectual Capital as Catalysts of Innovation: A Cross-Sectoral Perspective from Industry 4.0 to Hospitality Transformation - Anthonius S Hutabarat; Irawan R D Budianto; Hadita Hadita (Pusat Riset dan Inovasi Nasional, 2025)
The synergy between intellectual capital (IC) and absorptive capacity (ACAP) plays a crucial role in driving innovation across both manufacturing and service sectors. This paper bridges insights from Industry 4.0 and the AI- and 5G-enabled transformation of hospitality to explore how firms can leverage IC and ACAP for sustained innovation. Drawing upon a multidimensional conceptual framework, this study explores the dynamics between human, structural, and relational capital, and the potential and realized dimensions of ACAP in enhancing innovation performance. Industry 4.0’s emphasis on cyber-physical systems and data-driven manufacturing is juxtaposed with the hospitality sector’s pivot toward hyper-personalized services enabled by AI and 5G. The study reveals that both sectors share a dependence on dynamic knowledge capabilities, even as they diverge in application. This article proposes a sector-spanning integrative model of innovation and provides actionable managerial and policy-level recommendations to build knowledge-rich, adaptive, and innovation-driven organizations.